Contribution of genetic amplification by PCR for the diagnosis of Helicobacter pylori infection in patients receiving proton pump inhibitors. Issue 8 (1st October 2018) - Bazin, Thomas; Nchare Mfondi, Arouna; Julie, Catherine; Émile, Jean-François; Raymond, Josette; Lamarque, Dominique
Abstract : Background: Helicobacter pylori detection by standard methods may be altered by proton pump inhibitor (PPI) use. However, some patients cannot or should not interrupt PPI use before undergoing testing for H. pylori . Polymerase chain reaction (PCR) could allow more reliable H. pylori detection even in patients taking PPIs. Objective: The aim of our study is to compare the H. pylori infection diagnostic value of histological examination without and with immunohistochemical staining, bacterial culture and PCR, in PPI‐treated vs untreated patients. Methods: Patients undergoing a gastric endoscopy for upper digestive symptoms were included. Gastric biopsy samples were obtained. The impact of taking PPI on the diagnostic performance of the different methods was studied. PCR results were confirmed by sequencing the glmM gene. Results: A total of 497 patients were included, of whom 192 were H. pylori positive. Fifty‐two patients received PPIs during the 14 days preceding the endoscopy while 140 did not. All methods had lower sensitivity than PCR, in all cases (PPI treatment or not). PPI use did not change significantly the methods' sensitivities. Conclusion: The PCR method showed the best performance for the detection of H. pylori in gastric samples, whether or not patients received previous PPI treatment. This diagnosis test could become a new gold‐standard test, especially in patients undergoing PPI treatment.